Ameliorative effects of Scutellaria Pinnatifida subsp. pichleri (Stapf) Rech.f. Extract in streptozotocin-induced diabetic rats: chemical composition, biochemical and histopathological evaluation - Mehmet Salih Bakaç; Abdulahad Dogan; Mustafa Abdullah Yılmaz; Fikret Altındag; Fatih Donmez; Abdulhamit Battal (BMC, 2023)
Abstract Backgrounds Scutellaria Pinnatifida subsp. pichleri (Stapf) Rech.f. (SP) is used in folk medicine for the treatment of diabetes. The aim of the study was to determine the phenolic profile of SP extract (SPE) by LC-MS/MS and to investigate the antidiabetic, hepatoprotective and nephroprotective effects of SPE in streptozotosin (STZ)-induced diabetic rat model. Methods Forty-two rats were randomly divided into six groups (n = 7): Control (nondiabetic), diabetes mellitus (DM), DM + SP-100 (diabetic rats treated with SPE, 100 mg/kg/day), DM + SP-200 (diabetic rats treated with SPE, 200 mg/kg/day), DM + SP-400 (diabetic rats treated with SPE, 400 mg/kg/day) and DM + Gly-3 (diabetic rats treated with glibenclamide, 3 mg/kg/day). Live body weight, fasting blood glucose (FBG) level, antidiabetic, serum biochemical and lipid profile parameters, antioxidant defense system, malondyaldehyde (MDA) and histopathological examinations in liver, kidney and pancreas were evaluated. Results Apigenin, luteolin, quinic acid, cosmosiin and epigallocatechin were determined to be the major phenolic compounds in the SPE. Administration of the highest dose of SP extract (400 mg/kg) resulted in a significant reduction in FBG levels and glycosylated hemoglobin levels in STZ-induced diabetic rats, indicating an antihyperglycemic effect. SPE (200 and 400 mg/kg) and glibenclamide significantly improved MDA in liver and kidney tissues. In addition, SPE contributed to the struggle against STZ-induced oxidative stress by stimulating antioxidant defense systems. STZ induction negatively affected liver, kidney and pancreas tissues according to histopathological findings. Treatment with 400 mg/kg and glibenclamide attenuated these negative effects. Conclusions In conclusion, the extract of the aerial part of Scutellaria pinnatifida subsp. pichleri has hepatoprotective, nephroprotective and insulin secretion stimulating effects against STZ-induced diabetes and its complications due to its antidiabetic and antioxidant phytochemicals such as apigenin, luteolin, quinic acid, cosmosiin and epigallocatechin.